Analisis Keberlakuan Klausula Eksonerasi dalam Perjanjian Kredit Baku - I Dewa Ayu Komang Dinda Warsiki; Kadek Januarsa Adi Sudharma; I Gede Agus Kurniawan; Anak Agung Ayu Intan Puspadewi (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2026)
This study aims to analyze the applicability of exoneration clauses in the Indonesian legal system, particularly in banking credit agreements, through a review of their legal basis in the Civil Code, the Consumer Protection Law, and their application in practice based on the Gianyar District Court Decision Number 157/Pdt.G/2018/PN Gin. This analysis aims to assess the extent to which exoneration clauses align with the principles of contractual justice and consumer protection. The method used is normative legal research with a statutory approach and a case approach. Primary legal materials include the Civil Code, the Consumer Protection Law, the Banking Law, and court decisions, while secondary materials include legal literature and expert opinions. Data collection was carried out through library research. The analysis of legal materials was conducted descriptively and qualitatively with systematic, grammatical, and teleological interpretations to examine the validity and limitations of the use of exoneration clauses in standard credit agreements. The research findings indicate that exoneration clauses are still frequently found in credit agreements unilaterally drafted by banks. These clauses substantially limit the bank's liability and grant it unilateral authority in the implementation of the agreement, which in practice creates an imbalance in the bargaining position between the bank and the debtor. These clauses contradict Article 18 of the Consumer Protection Law (UUPK) because they contain provisions that shift responsibility and potentially violate the principle of good faith as stipulated in Article 1338 of the Civil Code. An analysis of the Gianyar District Court's decision shows that although the lawsuit was dismissed, the substance of the case demonstrates the practice of exoneration clauses that are detrimental to consumers, particularly related to the lack of information transparency and the bank's dominance in determining credit terms. The research conclusion confirms that exoneration clauses in standard credit agreements are not binding if they contradict the provisions of the UUPK or the principle of contractual balance.